The Application of Brainstorming Method in Developing Ideas in The Production of Television Documentary Side of Life Episode Not The Same - Eko Wahyuanto; Edi Giantoro; Joehananto Djoko Teguh Widodo; Risnaeni Yuniar (Technium Education and Humanities, 2024)
The Side Of Life Television Documentary Program episode Not The Same is a program that presents information about the issue of sexual harassment to men by women. Male victims of sexual harassment are often not believed and even made into a joke by society. This documentary program presents information through the victim as a resource person in providing a chronology of events and feelings of victims who are not trusted by family and society. The creation of this television documentary program production work aims to produce a television documentary program by maximizing the role of the producer in developing ideas by using the brainstorming method which aims to make the production run well and have clear and abundant information so that it can be understood by the audience. The writer as a producer focuses on how the producer’s creativity in developing ideas using the brainstorming method in television documentaries so that they can present information and knowledge. A television documentary program begins with some footage. Insert footage is used as the opening of the program followed by the program title and program episode. The Side Of Life program contains three sequences, each of which contains important and interesting information. Through the brainstorming method, it produces a program that is informative and becomes a medium for public education.